Association of Physical Activity with Psychological Distress and Poor Mental Health Days Among Informal Caregivers of Older Adults: Findings from the 2023 BRFSS Caregiver Module - Damián Pereira-Payo; Raquel Pastor-Cisneros; María Mendoza-Muñoz; Amparo Rodríguez-Gutiérrez (Healthcare, 2026)
Background/Objectives: Informal caregivers of older adults are a high-burden population for psychological problems, yet evidence on the relationship between physical activity (PA) and mental health in this population is still limited. The aim of this work is to examine the association between PA status and self-reported mental health indicators (psychological distress and the number of poor mental health days) among caregivers of older adults. Methods: This cross-sectional study used data from the 2023 Behavioral Risk Factor Surveillance System (BRFSS) caregiver module. The analytical sample included 1785 informal caregivers of older adults whose care recipients’ main condition was old age/infirmity/frailty or Alzheimer’s disease, dementia, or another cognitive impairment disorder. Physical activity was classified into three groups: meeting both aerobic and muscle-strengthening recommendations, reporting some PA but not meeting both recommendations, and being inactive. The self-reported mental health indicators were psychological distress (≥14 poor mental health days in the past 30 days) and the number of poor mental health days. Survey-weighted logistic regression and quasi-Poisson regression models were fitted, adjusting for sociodemographic, health-related, and caregiving-related covariates. Results: The weighted prevalence of psychological distress was 18.8%, and the mean of poor mental health days was 5.99 days in the previous 30 days. The weighted prevalence of psychological distress was 16.3% among caregivers meeting both recommendations, 18.2% among those reporting some PA, and 23.2% among inactive caregivers; however, differences across PA groups were not statistically significant. The weighted mean number of poor mental health days was 5.5, 6.2, and 6.1 days, respectively, with no significant differences across PA groups. In adjusted logistic regression models, physically inactive caregivers had higher odds of psychological distress than those meeting both activity recommendations (OR = 3.10, 95% CI: 1.58–6.09; p = 0.001). In adjusted quasi-Poisson models, physically inactive caregivers also reported more poor mental health days (RR = 1.51, 95% CI: 1.08–2.10; p = 0.016) compared to those who met both recommendations. No significant differences were observed for caregivers who met only aerobic recommendations or only muscle-strengthening recommendations, or had insufficient physical activity relative to the reference group. Conclusions: In this survey-weighted BRFSS caregiver-module sample from participating US jurisdictions, physical inactivity was associated with poorer self-reported mental health indicators among caregivers of older adults. These findings suggest that physical inactivity may help identify caregivers at higher risk of poorer self-reported mental health, although longitudinal and intervention studies are needed to clarify directionality and causality.